English as a Foreign Language Students’ Perception of the Emergence of Digital Platforms for Developing Listening Skills - Rendi Rendi; Yek Amin Aziz; Najamuddin Najamuddin (LPPM Universitas Bumigora Mataram, 2026)
The emergence of digital platforms has transformed the way English as a Foreign Language (EFL) students develop their listening skills. These platforms provide authentic listening materials, flexible access, and interactive features that support autonomous learning. This study employed a qualitative descriptive research method to explore students’ perceptions of using digital platforms for developing listening skills. The participants were 10 seventh-semester students of the English Education Study Program at the State Islamic University of Mataram. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that students perceive listening as a fundamental skill that supports other language skills, including speaking and vocabulary acquisition. Students reported using digital platforms such as YouTube, Spotify, Duolingo, TikTok, and English-language movies to improve their listening skills. These platforms were perceived as effective. However, students also encountered challenges, including rapid speech delivery, unfamiliar accents, limited vocabulary, unstable internet connections, and distractions. To overcome these challenges, students employed strategies such as slowing the audio and using subtitles. Overall, digital platforms play a significant role in supporting EFL students’ listening development when integrated effectively into instruction.